PERAN PENYULUH PERTANIAN DALAM MENINGKATKAN KAPASITAS PETANI PADI SAWAH DI KELURAHAN NGKARING-NGKARING KECAMATAN BUNGI KOTA BAUBAU - Wa Ode Putri Nabilah; Musadar Mappasomba; Salahuddin Salahuddin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
The involvement of agricultural extension workers in enhancing the capabilities of rice farmers in the rice fields includes crucial aspects to reinforce the effectiveness of agricultural management. Effective assistance from agricultural extension workers empowers rice farmers to improve their competencies in addressing challenges and opportunities in the agricultural sector. This study seeks to assess the impact of agricultural extension workers in Ngkaring-Ngkaring Village, Bungi District, Baubau City, to evaluate the proficiency of rice farmers in the same area, and to explore the correlation between the roles of agricultural extension workers and the abilities of rice farmers in Ngkaring-Ngkaring Village, Bungi District, Baubau City. The research was carried out between January and February 2024 with 49 respondents who are rice farmers in Ngkaring-Ngkaring Village. The variables measured include the roles of agricultural extension workers (educator, dissemination, facilitator, motivator) and farmers' capacities (social, managerial, technical). Data analysis utilized the class interval formula and Spearman's rank correlation. The study results reveal that the roles of agricultural extension workers are deemed adequate, with a 97.95% rating. The educator, dissemination, and motivator indicators are all classified as adequate at 97.95%, while the facilitator indicator is considered adequate at 95.92%. Farmer capacity is rated as good at 97.95%, with the social capacity indicator at 77.5%, managerial capacity at 57.14%, and technical capacity at 42.85%, all falling into the adequate category. There is a notable correlation between the roles of agricultural extension workers and farmers' capacities (educator (Sig = 0.041), dissemination (Sig = 0.034), facilitator (Sig = 0.028), motivator (Sig = 0.013).